Handbook of American romanticism - Löffler, Philipp; Spahr, Clemens; Stievermann, Jan (Handbooks of English and American studies, 2021)
Frontmatter -- The Editors’ Preface -- Contents -- 0 Introduction -- Part I: Definitions, Backgrounds, Contexts -- 1 Antebellum Period and Romanticism: Definitions and Demarcations -- 2 Antebellum Literary Culture: The Institutions of Romanticism -- 3 Transnational Dimensions of Romanticism -- 4 American Romanticism and Religion -- 5 Romanticism and European Philosophy, or “Idealism As It Appears in 1842” -- Part II: Intellectual, Spiritual, and Political Debates -- 6 Romanticism and Democracy -- 7 Romanticism and Social Reform -- 8 American Romanticism and Esotericism -- 9 America as Interior Space: Artificial Landscapes and the Modernization of Literature in Edgar Allan Poe’s Short Fiction -- Part III: Contestations of Authorship and Genre -- 10 Authorship as Profession and the Uses of Genre in Antebellum America -- 11 Poet-Prophets and Seers: American Romanticism, Authorship, and Literary Institutions -- 12 Life Writing and Romantic Expressivism -- 13 The Fireside and Sentimental Poets -- Part IV: Close Readings -- 14 Ralph Waldo Emerson’s Nature (1836): American Romantic “Manifesto” -- 15 Woman in the Nineteenth Century (1845): Romanticism and (Proto)Feminism -- 16 The Continuous Creation of Walden -- 17 Herman Melville’s Moby-Dick (1851) -- 18 Nathaniel Hawthorne’s The Scarlet Letter (1850) and the Historical Imagination in American Romanticism -- 19 Romanticism and History: Göttingen and George Bancroft’s History of the United States (1834) -- 20 Uncle Tom’s Cabin (1852) and the Politics of Sentimentalism -- 21 Myth and Mythmaking in the Douglass Circle -- 22 “The Soul Selects Her Own Society”: Emily Dickinson’s Poetry and the Creation of the Self -- 23 The Great Psalm of the Republic: Walt Whitman’s Democratic Poetics -- Part V: Reception Histories -- 24 Transcendentalist Legacies in American Philosophy -- 25 Rethinking Gender in Antebellum American Literature -- 26 “In the Woods We Return to Reason and Faith”: American Romanticism, Environmentalism, and Seeker Spirituality -- Index of Names -- Index of Subjects -- List of Contributors
Keywords: 1800-1999; United States; Geschichte 1790-1860; Romantik; Literatur; USA